Vertically oriented MoS2 nanoflakes coated on 3D carbon nanotubes for next generation Li-ion batteries. (9th November 2016) - Patel, Mumukshu D; Cha, Eunho; Choudhary, Nitin; Kang, Chiwon; Lee, Wonki; Hwang, Jun Yeon; Choi, Wonbong
Abstract: The advent of advanced electrode materials has led to performance enhancement of traditional lithium ion batteries (LIBs). We present novel binder-free MoS2 coated three-dimensional carbon nanotubes (3D CNTs) as an anode in LIBs. Scanning transmission electron microscopy analysis shows that vertically oriented MoS2 nanoflakes are strongly bonded to CNTs, which provide a high surface area and active electrochemical sites, and enhanced ion conductivity at the interface. The electrochemical performance shows a very high areal capacity of 1.65 mAh cm −2 with an areal density of 0.35 mg cm −2 at 0.5 C rate and coulombic efficiency of 99% up to 50 cycles. The unique architecture of 3D CNTs–MoS2 is indicative to be a promising anode for next generation Li-ion batteries with high capacity and long cycle life.